2020
DOI: 10.4102/jamba.v12i1.954
|View full text |Cite
|
Sign up to set email alerts
|

The role of knowledge and fatalism in college students related to the earthquake-risk perception

Abstract: At present, the earthquake-risk perception research in Aceh only focuses on the general public. Limited research examines earthquake-risk perceptions amongst students. This exploratory study is focused on geography education students because this study programme has integrated disaster education into its curriculum. This study aims to find the extent to which earthquake knowledge and fatalism beliefs affect earthquake-risk perception. The survey was conducted on 210 students using questionnaires. Using the Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 39 publications
4
19
0
1
Order By: Relevance
“…Given that stronger risk perception was positively associated with the intention to prepare, if disaster management policy is to be more effective in getting residents at least to intend to prepare for an earthquake, then campaigns should be constructed to carefully maximize risk perception and educate residents in order to enhance the motivation to prepare. The importance of education for reducing fatalism has been recommended by others (Aksa et al., 2020; Baytiyeh & Naja, 2016). In general, community members must be convinced that even if earthquakes are caused by nature, they can engage in actions that will soften the blow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that stronger risk perception was positively associated with the intention to prepare, if disaster management policy is to be more effective in getting residents at least to intend to prepare for an earthquake, then campaigns should be constructed to carefully maximize risk perception and educate residents in order to enhance the motivation to prepare. The importance of education for reducing fatalism has been recommended by others (Aksa et al., 2020; Baytiyeh & Naja, 2016). In general, community members must be convinced that even if earthquakes are caused by nature, they can engage in actions that will soften the blow.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of control over natural disasters can lead to fatalistic beliefs, and those who hold such beliefs tend to worry less about outcomes they see as beyond their control. Fatalists tend to perceive lower risk (Aksa, Utaya, Bachri, & Handoyo, 2020; Baytiyeh & Naja, 2016) and are more likely to be passive about hazard risks (Baytiyeh & Naja, 2016; Lehman & Taylor, 1987; Solberg et al., 2010; Turner, Nigg, & Paz, 1986). Farmers with greater risk perception were less likely to hold fatalist attitudes and therefore were more likely to intend to adapt to climate change (Hoa Le et al., 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research conducted by Bachri et al (2015) revealed that the Tengger people hold the belief that their lives are controlled by the Bromo volcano, which to a large extent explains why they choose—rather than being forced—to live with continued exposure to hazard risk. A recent survey conducted on 210 college students using questionnaires provided more evidence, and the results indicate that fatalism belief has a negative and significant effect on the perception of earthquake risk (Aksa et al, 2020). Therefore, our second hypothesis is as follows: boldHbold2 : Fatalism belief is negatively associated with risk perception.…”
Section: Theoretical Model and Research Hypothesesmentioning
confidence: 99%
“…However, even after 14 years, the programme has not been effective in increasing student capacity. This is evidenced by the findings of research conducted by Aksa et al (2020a), which uses case studies at several universities in Indonesia which are located in disaster-risk areas. Using regression analysis, it was found that educational institutions were ineffective in increasing student capacity in DRR.…”
Section: Introductionmentioning
confidence: 99%
“…Using regression analysis, it was found that educational institutions were ineffective in increasing student capacity in DRR. This is presumably because the disaster education taught so far only forms conceptual knowledge (know-what) so that students do not know how to do something (know-how) (Aksa et al 2020b(Aksa et al , 2020a. This is because of the traditional learning model being used which emphasises conceptual knowledge.…”
Section: Introductionmentioning
confidence: 99%